1993
DOI: 10.1104/pp.102.3.751
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Evidence for the Existence of a Carrier Protein for Sucrose Transport in Tonoplast Vesicles from Red Beet (Beta vulgaris L.) Root Storage Tissue

Abstract: .); and Hawaiian Sugar Planters' Association, Experiment Station, Aiea, Hawaii 96701 -1057 (A.M.) Monoclonal antibodies were raised in mice against a highly purified tonoplast fraction from isolated red beet (Befa vulgaris L.ssp. conditiva) root vacuoles. Positive hybridoma clones and subclones were identified by prescreening using an enzyme-linked immunosorbent assay (ELISA) and by postscreening using a functional assay. This functional assay consisted of testing the impact of hybridoma supernatants and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…, were able to inhibit SUC transport (Getz et al, 1993) and corresponding protonexport (Table I) to a comparable extent. This, together with successful reconstitution of a 55-kD polypeptide fraction, identified by use of these carrier-specific antibodies, into artificial proteoliposomes that then exhibited Suc transport activity (Thom et al, 1992;Getz et al, 1993Getz et al, ,1994 indicated close coupling between SUC and proton transport, probably mediated by the same carrier.…”
Section: Kinetics and Stoichiometry Of Suc/h+ Antiportmentioning
confidence: 91%
See 4 more Smart Citations
“…, were able to inhibit SUC transport (Getz et al, 1993) and corresponding protonexport (Table I) to a comparable extent. This, together with successful reconstitution of a 55-kD polypeptide fraction, identified by use of these carrier-specific antibodies, into artificial proteoliposomes that then exhibited Suc transport activity (Thom et al, 1992;Getz et al, 1993Getz et al, ,1994 indicated close coupling between SUC and proton transport, probably mediated by the same carrier.…”
Section: Kinetics and Stoichiometry Of Suc/h+ Antiportmentioning
confidence: 91%
“…Further evidence that Suc-induced medium acidification represented a translocation of Suc coupled to the efflux of H+ was obtained with monoclonal antibodies previously recognized as carrier specific and used for partia1 purification of the carrier, which was subsequently reinserted into artificial proteoliposomes (Thom et al, 1992;Getz et al, 1993Getz et al, , 1994. The monoclonal antibodies TNP5612 and C5,-,., had virtually no inhibitory effect on Suc-induced proton movement compared to mouse normal serum containing samples when applied at comparable dilutions after heat denaturation (Table I).…”
Section: Effect Of Lnhibitors and Carrier-specific Monoclonal Antibodmentioning
confidence: 99%
See 3 more Smart Citations